TEACHING ESP ONLINE: A SELF-REFLECTIVE THINKING PRACTICE - Tutut Nani Prihatmi (PROJECT (Professional Journal of English Education), 2022)
This article aimed at sharing the experiences of teaching English for Specific Purpose (ESP) for mechanical engineering students online during the COVID-19 pandemic. The aspects covered in this reflective thinking were the learning objectives, teaching strategies, student perceptions, and the learning problems and results from the author’s classroom. By using a narrative inquiry, the data used in this study were the teaching-learning documents, student’s video projects, and journal records. As the result, this study found that students' social environment at home affected their learning styles and outcomes. The author also suggests that other ESP teachers conduct more research on reflective practices that can help developing learning strategies and technology implemented in their courses.